Proposed Performance Management System Design Using IPMS (Integrated Performance Management System) Framework at PT Kereta Api Indonesia (Persero) - Ravenska, Nanda; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2016)
Abstract - PT Oranyeprima or hereinafter referred to company is the state-owned company that provides and manages railway transportation service. The company's goal is to implement and support government policies and programs in the field of economy and national development, by providing high quality and competitive goods and services. Therefore, to assist the achievement of national economic growth, then the company needs to manage its performance by producing a good service to contribute in increasing state revenues, and also be able to compete domestically and internationally. Currently, the performance management system implementation at PT Oranyeprima uses KPKU and Balanced Scorecard frameworks. The implementations of both methods are not effective and not fully implemented by the employees. Most employees do not understand the performance management system, and do not get the essence from the performance management system implementation. This study aims to provide the proposed performance management system design of PT Oranyeprima. PT Oranyeprima focus on meeting customer service according to the company's vision is to be the best railway service provider focusing on customer service and meeting stakeholder expectations. Mission of the company is undertaking the best business practices to create higher added value for the stakeholders. IPMS (Integrated Performance Management System) method was chosen as a performance management framework to be designed at PT Oranyeprima, because IPMS has focus successes in accordance with the vision, mission and objectives of the company which is the integration between aspects of financial and non-financial. IPMS is believed to be easily understood by the employees in the company. The author designed the performance indicators for the company based on three perspectives within IPMS namely: organizational result, internal processes, and resources capabilities. The performance indicators adjusted to the company's strategy in 2015. The performance indicators generated are related to profitability, customer, government and society, welfare and productivity of employees, operation processes, marketing, infrastructure, innovation and technological development. By implementing the performance management system using IPMS, the employees will more easily understand and motivated to implement the performance management system. In addition, the company will obtain a picture of the achievement of the company to date, and also the company can make continuous improvement and achieve the excellence performance.Â Keywords: IPMS, integrated performance management system, performance management system, railway industry, state-owned enterprise